Experiences in movement and music : birth to age eight - Pica, Rae (Pearson, Australia, 2013)
In the first edition of this text, I mentioned the dilemma I often face when asked what i do for a living. Whether i'am on an airplane en route to a presentation or at a social gathering, this seemingly innocent question has thrown me for a loop for years.
Part one : The Basic of movement education -- Part two : Planning for movement and music -- Part three : Facilitating movement experiences -- Part four : Movement and music through the day
Includes index.
Keywords: MOVEMENT EDUCATION; CHILD DEVELOPMENT